Peningkatan Kapasitas Masyarakat Desa Gema dalam Pengelolaan Air Bersih melalui Program Pengabdian kepada Masyarakat - Desrimon, Arfi; Setiawan, Beny; Sari, Delima; Tanjung, Lailatul Syifa (Journal of Social and Community Service, 2024)
The availability of clean water is a basic need that has not been fully met in Gema Village, Kampar Kiri District, Kampar Regency. Based on the results of observations, the quality of community well water is still low, especially in Hamlet II, with water that is cloudy, oily, and smelly. This problem is caused by the high content of iron, manganese, and organic materials, as well as the lack of community knowledge about clean water standards and processing techniques. This community service activity aims to improve community knowledge and skills in processing unsuitable water into water that can be used for household needs. The implementation method includes counseling, appropriate technology training, and direct assistance in the field. The results of the activity showed an increase in community understanding of the importance of clean water and the ability to assemble and use simple filters. The community was also active in the training process and monitoring the quality of processed water. This program has succeeded in providing a positive impact on the quality of life of the community and supporting the realization of a clean and healthy lifestyle in the village.